Manajemen Kurikulum dalam Proyek Penguatan Profil Pelajar Pancasila pada Sekolah Berbasis Pesantren di SMP Negeri 2 Kraton Pasuruan - Lailah Mawaddah; M. Fahim Tharaba; Indah Aminatuz Zuhriyah (EduInovasi: Journal of Basic Educational Studies, 2024)
This research examines curriculum management at SMP Negeri 2 Kraton, a pesantren-based school, in implementing the Pancasila Student Profile Strengthening Project. The study aims to understand the curriculum concept, project implementation, and its impact. A qualitative descriptive approach was employed in this research. The instruments used were interview guidelines and direct practices by the researcher. Data collection techniques included interviews, observations, and documentation. The collected data were analyzed descriptively using an interactive analysis model through data collection, data reduction, and conclusion drawing. The results of this study indicate that the Pancasila Student Profile Strengthening Project, in general, helps to enhance the competence and character of students by providing direct learning experiences about real life.